2019
DOI: 10.1007/s10816-019-09425-x
|View full text |Cite
|
Sign up to set email alerts
|

Material Principles and Economic Relations Underlying Neolithic Axe Circulation in Western Europe

Abstract: Neolithic societies produced and circulated axeheads made out of different rock types over substantial distances. These tools were indispensable to their economic reproduction, but they also demanded considerable manufacturing efforts. The material properties of the raw materials chosen to produce axeheads had a direct effect on the grinding and polishing processes, as well as on the use-life of these tools. However, surprisingly little is known about the criteria followed by these societies when it came to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…As rocks of good quality like phtanite seem to be exported over rather long distances (Mosel area, work in progress), others like silicified sandstone from Horion-Hozémont rarely leave their regional territory probably because of their complex manufacturing process, difficulty of collecting, etc. as recent studies concerning Western European axes tend to demonstrate (Delgado-Raack et al 2020)…”
Section: Introductionmentioning
confidence: 89%
“…As rocks of good quality like phtanite seem to be exported over rather long distances (Mosel area, work in progress), others like silicified sandstone from Horion-Hozémont rarely leave their regional territory probably because of their complex manufacturing process, difficulty of collecting, etc. as recent studies concerning Western European axes tend to demonstrate (Delgado-Raack et al 2020)…”
Section: Introductionmentioning
confidence: 89%
“…While buried valuables clearly represent wealth, employing the content of these deposits to characterize Bronze Age Europe political economies as financialized is altogether different. It seems far more plausible that the metal in Bronze Age hoards continued to be deposited for social/ symbolic purposes, comparable to stone axes during the Neolithic (e.g., Delgado-Raack et al, 2020;Thirault, 2005), even as the scale of such interactions expanded considerably (Vandkilde, 2016). Ialongo and Lago (2021) explicitly argue that European hoards were amassed financial wealth.…”
Section: Understanding European Bronze Age Moneymentioning
confidence: 99%
“…Renfrew, 1984), some individuals could have reached powerful positions through their control over the circulation of specific objects (e.g. Bradley & Edmonds, 1993;Delgado-Raack et al, 2020;Pétrequin et al, 2019). In this sense, these distribution networks can be understood as a social strategy that was used to establish and maintain important relationships by obtaining and circulating specific objects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even though the discussion concerning the 4th millennium BC exchange networks in Europe is more commonly associated with the agricultural societies (e.g. Bradley & Edmonds, 1993;Delgado-Raack et al, 2020;Ibáñez et al, 2016;Pétrequin et al, 2019), the giving and taking networks of the hunter-gatherer groups of north-eastern Europe seem to show evidence of a similar pattern in which local interaction was complemented by long-distance transactions by some of the participants (Herva et al, 2014;Kriiska, 2015;Tarasov & Nordqvist, 2021). For example, a recent study dealing with axes and adzes made of Lake Onega metatuff (Tarasov & Nordqvist, 2021) has suggested that these widely distributed items testify to the use of sophisticated technology and the specialised, large-scale production of objects intended for exchange.…”
Section: Introductionmentioning
confidence: 99%